Blacksmith: Between history, culture, and economy - Suryana, Aan; Pajriah, Sri; Fajriyah, Izzatul (Badan Kemitraan Inovasi dan Kewirausahaan Universitas Galuh, 2024)
This research was aimed at describing the historical, cultural, and economic value of blacksmith activities. The research method used was a literature study (library research). Data collection techniques were carried out through collecting research results that had been carried out and published in reputable indexed journals, Google Scholar, etc. The research results showed that blacksmithing had historical value whose development varied in each region of the world. In Asia, especially Indonesia, the historical development of blacksmithing was estimated to have existed since the 7th century AD. This was based on findings on temple wall reliefs, inscriptions, and ancient manuscripts found as relics from the royal era. Meanwhile, the historical development of blacksmiths in Europe, Africa, and other Asian regions was quite diverse, having developed from 1150-1400 BC. The blacksmiths of Dokdak Village also had cultural values ​​that were very important to be passed on. This was based on data which showed that in blacksmithing activities there were cultural elements, namely the knowledge system, livelihood system, and equipment and technology systems used. Furthermore, Dokdak Village's blacksmith activities had economic value, because the carried-out activities could produce production goods that have economic value. Based on this, it is important to protect and maintain the livelihood of blacksmiths to pass on values ​​to the younger generation.